2022
DOI: 10.53850/joltida.1020075
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Augmented Reality in the Technical Drawing Course on Engineering Students' Spatial Ability and Academic Achievement

Abstract: The purpose of this study is to investigate the effects of Augmented Reality (AR) intervention on students' spatial skills and academic achievement. The study was conducted in a freshman technical drawing course at Mechanical Engineering Department. An exploratory quasi-experimental method was used for the study. The study was conducted in two groups (Experiment-Control) as a quasiexperimental pre-post design. The pre-test results were used only to determine the control group and the experimental group. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…This assertion was echoed by Khoza (2013) and Makgato (2016) who found that learners are usually poor at spatial visualisation. Integrating technology into the classroom can be seen as the main reason for improving spatial skills (Akkuş & Arslan, 2022). It is contended that ICT integration in the teaching and learning of EGD is essential, and for that to be possible, teachers must be ready to infuse ICT.…”
Section: Factors Influencing Teachers' Ict Resistancementioning
confidence: 99%
“…This assertion was echoed by Khoza (2013) and Makgato (2016) who found that learners are usually poor at spatial visualisation. Integrating technology into the classroom can be seen as the main reason for improving spatial skills (Akkuş & Arslan, 2022). It is contended that ICT integration in the teaching and learning of EGD is essential, and for that to be possible, teachers must be ready to infuse ICT.…”
Section: Factors Influencing Teachers' Ict Resistancementioning
confidence: 99%
“…This is similar to Akkus & Arslan's (2022) quasi-experimental design where they studied how to use AR as an intervention in improving technical drawing skills by freshmen mechanical engineering students [21]. Their study revealed that the students who were in the intervention group that required the use of AR were very excited for the opportunity to use the new technology and indicated that the use of AR and the traditional paper simultaneously improved their technical drawing skills [21]. In another study, faculty created resources to aid engineering students in comprehending projection techniques using augmented reality which proved very useful because during the learning process the students demonstrated a higher degree of engagement [22].…”
Section: Ar In Engineeringmentioning
confidence: 92%
“…Chen et al, (2011) proposed an AR based system to aid students in an engineering graphics course by including instructions from the AR system so the students could individually control their learning process through the development of spatial abilities [20]. This is similar to Akkus & Arslan's (2022) quasi-experimental design where they studied how to use AR as an intervention in improving technical drawing skills by freshmen mechanical engineering students [21]. Their study revealed that the students who were in the intervention group that required the use of AR were very excited for the opportunity to use the new technology and indicated that the use of AR and the traditional paper simultaneously improved their technical drawing skills [21].…”
Section: Ar In Engineeringmentioning
confidence: 99%